Services trade and labour market outcomes in the United Kingdom - Lassmann, Andrea (OECD Publishing, 2020)
Services trade has become increasingly important, yet its impact on employment has been understudied at present. This paper uses fine-grained data on firm- and worker-level information to shed light on the impact of services trade on employment and wages in the United Kingdom. It finds that firms can benefit from services trade, through increased employment, production and productivity. On average, workers' wages are also positively impacted by increased services trade. The findings suggest that services imports enhance female wages more than those of males, thereby contributing to narrow the gender wage gap. They also suggest that reduction of services trade barriers in foreign markets with which the United Kingdom trades coincides with higher wages for employees of trading firms in the United Kingdom
Keywords: Trade; United Kingdom